Los conceptual maps - Giraldo Enciso, Iván (2017)
The present work seeks to imply a versatile tool for the work of teachers in their classrooms. In our teaching practice we have applied this teaching-learning strategy with good results, so that the teacher who applies it will have obvious achievements in their students.